The Influence of Academic Supervision and School Principal Leadership Style on Performance of State Junior High School Teachers in The Sub-District Bandar District Bener Meriah - Rizki Kusuma Dewi; Nasir Usman; Khairuddin Khairuddin (JETL (Journal of Education, Teaching and Learning), 2023)
Enhancing the quality of education heavily relies on the involvement of human resources in education. The pivotal role of teachers in facilitating student learning and development towards producing competent human resources is undeniable. Effective teacher performance is paramount in ensuring the quality of education in schools. Therefore, enhancing teacher performance requires comprehensive and serious measures, including academic supervision and the application of suitable leadership styles by school principals. This research aims to evaluate the individual and combined effects of academic supervision and leadership styles of school principals on the performance of public junior high school teachers in the Bandar District of Bener Meriah Regency. Using a quantitative approach and a questionnaire for data collection, the study reveals that while academic supervision has no significant impact on teacher performance, the leadership style of school principals has a significant effect on the performance of junior high school teachers. Moreover, both academic supervision and the leadership style of school principals simultaneously contribute significantly to the performance of public junior high school teachers in the Bandar District of Bener Meriah Regency, as confirmed by an F-test value of (17.181) > F-table (3.160) and a p-value of (0.000) < α (0.05). This implies that better academic supervision and leadership styles of school principals lead to better teacher performance in schools.